Development and evaluation of flashcards as a learning media for Arabic vocabularies in Islamic elementary education - Salma, Qatrunnada Habibah; Inayah, Inayah; Adriyani, Zuanita; Saadah, Fina (LP2M IAIN Sultan Amai Gorontalo, 2026)
Background: Arabic vocabulary instruction in Islamic elementary schools (Madrasah Ibtidaiyah) is often hindered by low student motivation and a reliance on rote memorization, which is particularly ineffective for concrete themes like diseases (al-amrāḍ). This highlights a critical need for developmentally appropriate visual media. Aims: This research aims to: (1) design thematic flashcard media on al-amrāḍ for third-grade students, (2) evaluate the media's validity through expert judgment, and (3) assess its practicality and impact on student engagement. Methods: Employing a Research and Development (R&D) framework, this study utilized the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The process began with a needs analysis through observation and interviews, followed by the design and validation of flashcards by experts in Arabic language education, media, and linguistics. A limited trial with 22 third-grade students at MI Miftahul Akhlaqiyah, Semarang, was conducted to evaluate practicality and student perceptions through observation and response questionnaires. Results: The flashcards achieved high validity scores from experts: 88% (content), 83% (linguistics), and 75% (media). Student responses were exceptionally positive, with an overall practicality rating of 95%, particularly appreciating the visual appeal, ease of use, and increased motivation. The findings indicate that the flashcards effectively facilitate vocabulary acquisition by creating clear visual-lexical connections. Implications: The al-amrāḍ flashcards are a valid and practical learning medium that effectively addresses pedagogical gaps in elementary Arabic instruction. This research underscores the importance of integrating visual design with linguistic accuracy for young learners. Practically, the flashcards offer an engaging, interactive alternative to traditional methods. Theoretically, it contributes to the discourse on multimedia design for early language acquisition within religious education contexts.